Adolescent Mentoring on Dysmenorrhea in Pucak Village, Tompobulu District, Maros Regency - Ruqaiyah Ruqaiyah; Fatmawati Amir; Hasrah Ibrahim (Universitas AMIKOM Yogyakarta, 2025)
Dysmenorrhea is a common menstrual disorder among adolescents, characterized by lower abdominal pain occurring before or during menstruation. Limited knowledge about dysmenorrhea among young women in rural areas often leads to inadequate management and disruption of daily activities. This community service program aimed to improve adolescent girls' knowledge regarding dysmenorrhea—including its definition, causes, prevention, and treatment—in Pucak Village, Tompobulu District, Maros Regency. The activity was conducted on January 13–17, 2025, involving 27 adolescent girls as participants. Methods consisted of health education using lectures and question-and-answer sessions, supported by leaflets. Pre- and post-test assessments were used to measure knowledge improvement. The results showed a significant increase in participants' knowledge: before the intervention, only 30% of participants had adequate knowledge about dysmenorrhea, its causes, prevention, and treatment; after the mentoring program, this proportion increased to 90%. The program was well-supported by local government officials, community leaders, and health center staff. The activity demonstrated that structured health education delivered through community mentoring is effective in improving reproductive health literacy among adolescent girls.